ANIMAL VENOM FOR TREATING BREAST CANCER - Ahluwalia, Sanchita; Shah, Nakul (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Breast cancer is one of the most common malignancies found in women and is associated with increased mortality in advanced disease. With the use of improved screening techniques and improvisation in treatment, 89% of the women diagnosed with breast cancer will survive 5 years from diagnosis. Despite significant advancement in the diagnosis and treatment of breast cancer, many patients succumb to this disease. The elucidation of aberrant signaling pathways that lead to breast cancer should help develop more effective therapeutic strategies. This review focuses on the different targets of breast cancer and how they can be acted upon by different animal venoms.